Multi-scales simulations of Monsoon rains and heat waves seasonality in West Africa - (:unkn) unknown (My University, 2018)
This thesis deals with the study of the climate of West Africa using the global model developed at the Pierre Simon Laplace Institute and observations mainly acquired during the Multidisciplinary Analysis campaign of the African Monsoon AMMA. The work of the thesis aims more specifically at improving the representation of the West African climate by reducing the biases observed in the intercomparison exercise of coupled models CMIP5, in particular from atmosphere-surface interactions, with the aim of better predict the distribution of rainfall over the region but also extreme events such as heat waves. The results showed that the representation of seasonality of temperatures and rainfall in West Africa was altered by strong biases on the surface energy budget and large-scale circulation (latitudinal positioning of the key elements of the monsoon). The first part of the work consists of implementing an evaluation technique based on two experimental protocols and aimed at: i) distinguishing the biases due to the circulation of those due to the energy budget at the surface, ii) facilitating the exploitation of data on sites, iii) isolating the effect of parameterizations. In this section, the biases on circulation and water budget are illustrated. This study first demonstrates the great interest of the nudging method for the confrontation of a GCM with station data and for analyzing the effect of model parameterizations in West Africa. Then, The in-situ data are used to: 1) identify the biases on the energy budget, 2) link these biases to the defects of the parameterizations used in order to find ways to improve. With this study, a number of problems, such as a poor specification of bare soil albedo and different plant functional type or "bug" in the coupling between thermal inertia and soil moisture have been identified . Some are now corrected in recent versions of the model developed for the CMIP6 exercise. Also in this manuscript, we show the progress
Keywords: African Research